Implementasi Penilaian Daur Hidup Produk Susu Sapi Segar (Studi Kasus Koperasi Peternak MJM) - Bunga Cahyaputri; Mohamad Yani; Sugiarto Sugiarto (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
The growth of the milk industry in Indonesia is increasing every year. This is due to population growth, Indonesian income increasing, and their awareness of consuming milk benefit. Milk production in Indonesia comes from small and medium-term farmers, requiring Koperasi to improve the quality of dairy products in Indonesia. Koperasi Mitra Jaya Mandiri (MJM) consists of dozens of small local farm which all activities are still done manually. Activities of Koperasi MJM, farmers and milk transportation have an impact on the environment. The objective of this research is identify inputs, outputs and environmental impacts in the production of 1 kg of fresh milk (case study of Koperasi MJM). The methods used are life cycle assessment (LCA) with three impact categories: global warming (GWP), eutrophication potential (EP) and acidification potential (AP). The boundary of LCA study is